Benchmarking the Current Employment Statistics survey: perspectives on current research. - Robertson, Kenneth W. (Monthly Labor Review, 2017)
The article looks at benchmarking in the Current Employment Statistics (CES) survey conducted by the U.S. Bureau of Labor Statistics (BLS), from its history from 1935 to current benchmark procedures. It describes the general practice of CES benchmarking and presents quantitative results at national and state levels. An overview of methods included in recent employment research is provided, as well as impediments to improving the method.